The Use of Tempeh in the Instant Tempeh Pudding as Functional Food - Alsuci Lestari; Rosi Novita; Rachmawati Rachmawati; Erwandi Erwandi (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
Additional food feeding has limitations in terms of processing and variations. However, it can be modified in various forms by utilizing tempeh, a highly functional food ingredient. This study aims to (1) explore the acceptability of instant tempeh pudding based on the parameters of color, taste, aroma, and texture, and (2) analyze the content of the chemical test including water, ash, protein, fat, and carbohydrate content. This research employed an experimental design and a completely randomized design (CRD). Chemical properties were analyzed using the proximate method. Meanwhile, the organoleptic properties were analyzed using the hedonic test. This study employed 30 moderately trained panelists and conducted a statistical analysis using the ANOVA test and Duncan's follow-up test (DMRT). This research was conducted in June 2021 at the Organoleptic Laboratory and Goods Quality Testing and at the Certification Center to analyze chemical properties. The organoleptic test examined the categories of color, taste, aroma, and texture of three pudding treatments with the addition of 80 grams (A1), 100 grams (A2), and 120 grams (A3) of tempeh flour. The chemical test has discovered that the average water content of the pudding from the three treatments is 67.1–69.8, the ash content is 0.63-0.68, the protein is 3.80-4.22, the fat is 0.28-0.47, and the carbohydrates are 24.9-27.7%. The addition of 80 grams, 100 grams, and 120 grams of tempeh flour does not significantly affect the organoleptic properties of the pudding. Finally, the chemical analysis shows that the addition of 80 gr, 100 gr, and 120 grams of tempeh flour significantly affects water and carbohydrate content but does not significantly affect ash, protein, and fat content.